Has the COVID-19 Pandemic Changed the Way Travel Agencies Clients’ Make Decisions? - Jaremen, Daria E.; Michalska-Dudek, Izabela; Pellešová, Pavlina (Publishing House of Wroclaw University of Economics and Business, 2024)
The main goal of this chapter was to identify changes in the decision-making process regarding the purchase of package tours in three different periods: before, during and after the COVID-19 pandemic. Identifying these changes will allow both researchers and practitioners to better understand the evolution of consumer behaviour and adapt business strategies to changing market realities. To achieve the research goal, a literature search was conducted and field research was undertaken (N2020 = 1.502 and N2022 = 1.508). In the case of secondary sources, the method of content analysis was used in the adopted research area. Descriptive statistics methods were used to analyse data from primary sources collected using the indirect survey technique (CAWI).
Jaremen, D. E., Michalska-Dudek, I., & Pellešová, P. (2024). Has the COVID-19 Pandemic Changed the Way Travel Agencies Clients’ Make Decisions?. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), The Importance of Universities for Society and Economy. The Experience of Researchers from the Visegrád Group (pp. 207-216). Publishing House of Wroclaw University of Economics and Business.
Keywords: customer behaviour; package holidays; travel agency; COVID-19 pandemic